Polymer dispersant and preparation method thereof, electrode slurry, electrode plate and battery
By adding polymer dispersant to the positive electrode slurry of lithium-ion batteries, the problem of poor viscosity stability of the slurry at lower viscosity is solved, and better coating performance and electrode sheet performance are achieved.
Patent Information
- Application Number
- CN202410408055.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-07
- Publication Date
- 2025-04-15
AI Technical Summary
The positive electrode slurry of lithium-ion batteries has poor viscosity stability at lower viscosity, resulting in uneven coating and degradation of electrode sheet performance.
The dispersant is prepared by polymerization reaction using a polymerization reaction, and added to the positive electrode slurry of a lithium-ion battery to adjust the viscosity and stability of the slurry.
Maintain good slurry stability at lower viscosity, reduce the risk of scratches in coating, and improve the appearance quality and charging performance of the pole sheet.
Smart Images

Figure CN119823328A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer dispersant and a preparation method thereof, an electrode slurry, an electrode plate and a battery. Background Art
[0002] Lithium-ion battery is an important battery technology, widely used in electric vehicles, mobile phones, laptops, etc. It has become the mainstream technology in the current battery field due to its advantages such as high energy density, long cycle life and low self-discharge rate.
[0003] Lithium-ion battery is a complex system, including positive electrode, negative electrode, separator, electrolyte, current collector, binder, conductive agent, etc. The reactions involved include electrochemical reaction of positive and negative electrodes, lithium ion conduction and electron conduction, as well as heat diffusion. Its production process is relatively long, and is mainly divided into pole piece production (front section), battery cell assembly (middle section), battery cell activation detection and battery packaging (back section) according to the corresponding equipment. In these three stages of the process, each process can be divided into several key processes, and each step will have a great impact on the final performance of the battery.
[0004] In the stage of pole piece production, the coating process is a key step to speed up. When exposed to the air, the positive electrode slurry easily absorbs moisture in the air, and the binder condenses, which increases the viscosity of the slurry. In addition, particle sedimentation and agglomeration may also increase the viscosity. The slurry viscosity itself does not affect the performance of the battery cell, but it has a greater impact on the slurry stability, and the viscosity can cause various problems in coating. As the viscosity increases, the slurry stability increases accordingly, but the slurry viscosity is too high, and scratches are easily generated during subsequent coating. On the one hand, it causes the pole piece to have a poor appearance, and on the other hand, it is easy to cause negative electrode lithium deposition during the charging process.
[0005] Therefore, how to obtain a positive electrode slurry with low viscosity but good stability is of great significance to the art. Summary of the invention
[0006] The present invention is mainly to overcome the defect of poor viscosity stability of the positive electrode slurry of lithium ion batteries in the prior art at a relatively low viscosity, and provides a polymer dispersant and a preparation method thereof, an electrode slurry, an electrode plate and a battery. When the polymer dispersant provided by the present invention is applied to the positive electrode slurry of a lithium ion battery, it can maintain good stability at a relatively low viscosity.
[0007] In order to overcome the above technical problems, the present invention provides the following technical solutions.
[0008] In a first aspect, the present invention provides a method for preparing a polymer dispersant, comprising the following steps:
[0009] The raw material composition is subjected to a polymerization reaction to obtain the polymer dispersant; the raw material composition comprises a reaction monomer, an initiator and a solvent; the reaction monomer comprises a monomer A, a monomer B, a monomer C and a monomer D, wherein, based on the total mass of the reaction monomers, the mass percentage of the monomer A is 6-10%; the mass percentage of the monomer B is 34-50%; the mass percentage of the monomer C is 20-30%; and the mass percentage of the monomer D is 20-30%;
[0010] The monomer A is one or more selected from acrylic acid, methacrylic acid, maleic acid, and fumaric acid;
[0011] The monomer B is selected from one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate, polyethylene glycol polypropylene glycol diacrylate, polyethylene glycol polypropylene glycol dimethacrylate, methoxy polyethylene glycol methyl methacrylate, allyl polyethylene glycol, methallyl polyethylene glycol, isopentenyl polyethylene glycol, and 4-hydroxybutyl vinyl polyethylene glycol;
[0012] The monomer C is one or more selected from N,N-dimethylaminoethyl acrylic acid hydrochloride, N,N-dimethylaminoethyl acrylic acid sulfate, β-aminoethyl methacrylic acid hydrochloride, β-aminoethyl methacrylic acid sulfate, N,N-dimethylaminoethyl methacrylic acid hydrochloride, N-vinyl pyridinium salt, N-vinyl pyrrolidone and N-acryloylmorpholine;
[0013] The monomer D is one or more selected from isooctyl acrylate, decyl methacrylate, isodecyl methacrylate, dodecyl methacrylate, dodecyl acrylate, heptadecanyl methacrylate, heptadecanyl acrylate, octadecyl methacrylate, octadecyl acrylate, behenyl methacrylate, behenyl acrylate, 2-propylheptyl acrylate, 2-propylheptyl methacrylate, and 2-phenoxyethyl methacrylate.
[0014] In the present invention, the monomer B may be one or more selected from polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate, polyethylene glycol polypropylene glycol diacrylate, polyethylene glycol polypropylene glycol dimethacrylate, allyl polyethylene glycol, methallyl polyethylene glycol, isopentenyl polyethylene glycol and 4-hydroxybutyl vinyl polyethylene glycol.
[0015] In the present invention, the monomer D may be one or more selected from isooctyl acrylate, decyl methacrylate, isodecyl methacrylate, dodecyl methacrylate, dodecyl acrylate, heptadecanyl methacrylate, octadecyl methacrylate, octadecyl acrylate, behenyl methacrylate, behenyl acrylate, 2-propylheptyl acrylate, 2-propylheptyl methacrylate and 2-phenoxyethyl methacrylate.
[0016] In the present invention, based on the total mass of the reaction monomers, the mass percentage of the monomer A is 6-10%; the mass percentage of the monomer B is 39-50%; the mass percentage of the monomer C is 20-28%; the mass percentage of the monomer D is 20-30%;
[0017] The monomer A is one or more selected from acrylic acid, methacrylic acid, fumaric acid and maleic acid;
[0018] The monomer B is one or more selected from methoxy polyethylene glycol methyl methacrylate, isopentenyl polyethylene glycol, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate and polyethylene glycol polypropylene glycol diacrylate;
[0019] The monomer C is one or more selected from N-vinyl pyrrolidone, β-aminoethyl methacrylate sulfate, N-vinyl pyridinium salt and N-acryloyl morpholine;
[0020] The monomer D is one or more selected from octadecyl methacrylate, heptadecanyl acrylate and behenyl acrylate.
[0021] In some specific embodiments, based on the total mass of the reactive monomers, the mass percentage of the monomer A may be 6%, 7%, 8%, 9% or 10%.
[0022] In some specific embodiments, based on the total mass of the reactive monomers, the mass percentage of the monomer B may be 39%, 41%, 42%, 43%, 49% or 50%.
[0023] In some specific embodiments, based on the total mass of the reactive monomers, the mass percentage of the monomer C may be 20%, 22%, 23%, 25% or 28%.
[0024] In some specific embodiments, based on the total mass of the reactive monomers, the mass percentage of the monomer D may be 20%, 23%, 25%, 26% or 28%.
[0025] In some specific embodiments, based on the total mass of the reactive monomers, the mass percentage of the monomer A is 6-10%, the mass percentage of the monomer B is 38-50%, the mass percentage of the monomer C is 20-30%, and the mass percentage of the monomer D is 20-28%.
[0026] In some specific embodiments, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 6%-8%; monomer B: 39%-46%, wherein monomer B is methoxy polyethylene glycol methyl methacrylate; monomer C: 23%-25%; and monomer D: 23%-30%.
[0027] In some preferred embodiments, based on the total mass of the reaction monomers, the reaction monomers include: monomer A: 7%-10%; monomer B: 40%-45%, wherein monomer B is isopentyl polyethylene glycol; monomer C: 22%-24%; and monomer D: 25%-30%.
[0028] In some preferred embodiments, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 8%-10%; monomer B: 48%-50%, wherein monomer B is polypropylene glycol diacrylate; monomer C: 20%-24%; and monomer D: 20%-24%.
[0029] In some preferred embodiments, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 6%-8%; monomer B: 39%-43%, wherein monomer B is polypropylene glycol dimethacrylate; monomer C: 25%-29%; and monomer D: 23%-30%.
[0030] In some preferred embodiments, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 6%-8%; monomer B: 40%-45%, wherein monomer B is polyethylene glycol polypropylene glycol diacrylate; monomer C: 20%-25%; and monomer D: 23%-30%.
[0031] In some specific embodiments, the reactive monomers include 6% acrylic acid, 39% methoxypolyethylene glycol methyl methacrylate, 25% N-vinyl pyrrolidone, and 30% octadecyl methacrylate based on the total mass of the reactive monomers.
[0032] In some specific embodiments, the reactive monomers include 8% acrylic acid, 46% methoxypolyethylene glycol methyl methacrylate, 23% β-aminoethyl methacrylate sulfate, and 23% octadecyl methacrylate based on the total mass of the reactive monomers.
[0033] In some specific embodiments, the reactive monomers include 9% methacrylic acid, 42% isopentenyl polyethylene glycol, 23% N-vinyl pyridinium salt, and 26% octadecyl methacrylate based on the total mass of the reactive monomers.
[0034] In some specific embodiments, the reactive monomers include 10% fumaric acid, 50% polypropylene glycol diacrylate, 20% N-vinyl pyrrolidone, and 20% heptadecanyl acrylate based on the total mass of the reactive monomers.
[0035] In some specific embodiments, the reactive monomers include 6% methacrylic acid, 41% polypropylene glycol dimethacrylate, 28% N-vinyl pyrrolidone, and 25% behenyl acrylate based on the total mass of the reactive monomers.
[0036] In some specific embodiments, the reactive monomers include 7% maleic acid, 43% polyethylene glycol polypropylene glycol diacrylate, 22% N-acryloylmorpholine, and 28% octadecyl acrylate based on the total mass of the reactive monomers.
[0037] In the present invention, the polymerization reaction temperature may be 85-95°C.
[0038] In the present invention, the solvent can be any conventional solvent in the art, preferably N-methylpyrrolidone.
[0039] In the present invention, the type of the polymerization reaction may be free radical random polymerization.
[0040] In the present invention, the initiator may be one or more of cumene hydroperoxide, tert-butyl hydroperoxide, azobisisobutyronitrile and azobisisoheptanenitrile conventionally used in the art for initiating free radical polymerization.
[0041] In the present invention, the raw material composition may further comprise a chain transfer agent, and the chain transfer agent may be one or more of 2-mercaptoethanol, n-butyl mercaptan, tert-butyl mercaptan, and dodecyl mercaptan.
[0042] In a second aspect, the present invention provides a polymer dispersant prepared by the preparation method as described above.
[0043] In the present invention, the weight average molecular weight of the polymer dispersant may be 5000-50000, for example, 33581, 28450, 42420, 18340, 35530 or 10240.
[0044] In the present invention, the polymer dispersant may be a random copolymer.
[0045] In the present invention, the molecular weight distribution index of the polymer dispersant may be 1.2-2, for example, 1.97, 1.65, 1.86, 1.75, 1.99 or 1.35.
[0046] In a third aspect, the present invention provides an electrode slurry comprising an electrode active material, the polymer dispersant as described above, and a solvent.
[0047] In the present invention, the electrode active material is preferably a positive electrode active material. The positive electrode active material is preferably one or more of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, nickel cobalt manganese ternary material, and nickel cobalt aluminum oxide lithium ternary material.
[0048] Wherein, the electrode slurry preferably further includes a conductive agent; the conductive agent is preferably one or more of carbon black or carbon nanotubes.
[0049] In a fourth aspect, the present invention provides an electrode plate, which is made using the electrode slurry as described above.
[0050] In the present invention, the method for preparing an electrode plate using the electrode slurry can be conventional in the art, and generally comprises: coating the electrode slurry on at least one surface of a current collector, and drying.
[0051] In a fifth aspect, the present invention provides a battery comprising the electrode plate as described above.
[0052] In the present invention, the battery is preferably a lithium ion battery.
[0053] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0054] The reagents and raw materials used in the present invention are commercially available.
[0055] The positive and progressive effects of the present invention are:
[0056] (1) When the polymer dispersant prepared by the preparation method provided by the present invention is applied to the positive electrode slurry of a lithium battery, a small amount of polymer dispersant is added to achieve good slurry stability, and the viscosity rebound of the slurry is low after 24 hours, maintaining good processing performance. In some preferred embodiments, the initial slurry viscosity is below 9600 mPa·s, and the 24h slurry viscosity is also below 12800 mPa·s.
[0057] (2) Furthermore, the electrode piece obtained by adding the polymer dispersant of the present invention has lower resistivity and better peel strength, and can also obtain good flexibility.
[0058] In some preferred embodiments, the resistivity of the electrode can be 36.7 Ω·cm -1, the peel strength can be 29.0N / m. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is the infrared spectrum of the polymer dispersant prepared in Example 1.
[0060] Figure 2 This is the molecular weight distribution diagram of the polymer dispersant prepared in Example 1. DETAILED DESCRIPTION
[0061] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0062] All parts in the following examples are by mass, and the manufacturer information of some raw materials is shown in the following table.
[0063]
[0064] Example 1
[0065] 6 parts of acrylic acid, 39 parts of methoxypolyethylene glycol methyl methacrylate, 25 parts of N-vinyl pyrrolidone, 30 parts of octadecyl methacrylate and 25 parts of N-methyl pyrrolidone were dissolved to obtain a mixed monomer, 0.5 parts of initiator and 0.5 parts of chain transfer agent were added to 25 parts of N-methyl pyrrolidone to obtain an initiator solution, 50 parts of N-methyl pyrrolidone were added to the reactor, the temperature was raised to 90°C, and the mixed monomer and initiator solution were added dropwise at a uniform rate for 5 hours. After the addition was completed, the temperature was kept constant for 1 hour, the temperature was lowered and the material was filtered to prepare a polymer dispersant. The weight average molecular weight detected by GPC was 33581, and the polydispersity coefficient was 1.97.
[0066] Example 2
[0067] 8 parts of acrylic acid, 46 parts of methoxypolyethylene glycol methyl methacrylate, 23 parts of β-aminoethyl methacrylate sulfate, 23 parts of octadecyl methacrylate and 25 parts of N-methylpyrrolidone were dissolved to obtain a mixed monomer, 0.6 parts of initiator and 0.3 parts of chain transfer agent were added to 25 parts of N-methylpyrrolidone to obtain an initiator solution, 50 parts of N-methylpyrrolidone were added to the reactor, the temperature was raised to 85°C, and the mixed monomer and initiator solution were added dropwise at a uniform rate for 5 hours. After the addition was completed, the temperature was kept constant for 1 hour, the temperature was lowered and the material was filtered to prepare a polymer dispersant. The weight average molecular weight was 28450 and the PDI was 1.65.
[0068] Example 3
[0069] 9 parts of methacrylic acid, 42 parts of isopentenyl polyethylene glycol, 23 parts of N-vinyl pyridinium salt, 26 parts of octadecyl methacrylate and 25 parts of N-methylpyrrolidone were dissolved to obtain a mixed monomer, 0.5 parts of initiator and 0.5 parts of chain transfer agent were added to 25 parts of N-methylpyrrolidone to obtain an initiator solution, 50 parts of N-methylpyrrolidone were added to the reactor, the temperature was raised to 88°C, and the mixed monomer and initiator solution were added dropwise at a uniform rate for 5 hours. After the addition was completed, the temperature was kept constant for 1 hour, the temperature was lowered and the material was filtered to prepare a polymer dispersant. The weight average molecular weight detected by GPC was 42420 and the PDI was 1.86.
[0070] Example 4
[0071] Dissolve 10 parts of fumaric acid, 50 parts of polypropylene glycol diacrylate, 20 parts of N-vinyl pyrrolidone, 20 parts of acrylate heptadecanol and 25 parts of N-methyl pyrrolidone to obtain a mixed monomer, add 0.6 parts of initiator and 0.2 parts of chain transfer agent to 25 parts of N-methyl pyrrolidone to obtain an initiator solution, add 50 parts of N-methyl pyrrolidone to the reactor, raise the temperature to 92°C, and start to drip the mixed monomer and initiator solution at a uniform rate for 5 hours. After the dripping, continue to keep warm for 1 hour, cool and filter the material to prepare a polymer dispersant. The GPC detection weight average molecular weight is 18340 and the PDI is 1.75.
[0072] Example 5
[0073] Dissolve 6 parts of methacrylic acid, 41 parts of polypropylene glycol dimethacrylate, 28 parts of N-vinyl pyrrolidone, 25 parts of docosyl acrylate and 25 parts of N-methyl pyrrolidone to obtain a mixed monomer, add 0.5 parts of initiator and 0.5 parts of chain transfer agent to 25 parts of N-methyl pyrrolidone to obtain an initiator solution, add 50 parts of N-methyl pyrrolidone to the reactor, raise the temperature to 94°C, and start to drip the mixed monomer and initiator solution at a uniform rate for 5 hours. After the dripping is completed, continue to keep warm for 1 hour, cool down and filter the material to prepare a polymer dispersant. The GPC detection weight average molecular weight is 35530 and the PDI is 1.99.
[0074] Example 6
[0075] Dissolve 7 parts of maleic acid, 43 parts of polyethylene glycol polypropylene glycol diacrylate, 22 parts of N-acryloylmorpholine, 28 parts of octadecyl acrylate and 25 parts of N-methylpyrrolidone to obtain a mixed monomer, add 0.8 parts of initiator and 0.3 parts of chain transfer agent to 25 parts of N-methylpyrrolidone to obtain an initiator solution, add 50 parts of N-methylpyrrolidone to the reactor, raise the temperature to 90°C, and start to drip the mixed monomer and initiator solution at a uniform speed for 5 hours. After the dripping is completed, continue to keep warm for 1 hour, cool and filter the material to prepare a polymer dispersant. The GPC detection weight average molecular weight is 10240 and the PDI is 1.35.
[0076] Comparative Example 1
[0077] Polyvinyl pyrrolidone (PVP K30) commonly available on the market was used as a dispersant.
[0078] Comparative Example 2
[0079] Dissolve 4 parts of acrylic acid, 40 parts of methoxypolyethylene glycol methyl methacrylate, 5 parts of N-acryloylmorpholine, 51 parts of isooctyl acrylate and 25 parts of N-methylpyrrolidone to obtain a mixed monomer, add 0.8 parts of initiator and 0.3 parts of chain transfer agent into 25 parts of N-methylpyrrolidone to obtain an initiator solution, add 50 parts of N-methylpyrrolidone into a reactor, raise the temperature to 90°C, start to drip the mixed monomer and initiator solution at a uniform speed, the dripping time is 5 hours, keep warm for 1 hour after the dripping is completed, cool and filter the material to prepare a polymer dispersant.
[0080] Comparative Example 3
[0081] Dissolve 4 parts of acrylic acid, 70 parts of methoxypolyethylene glycol methyl methacrylate, 5 parts of N-acryloylmorpholine, 21 parts of isooctyl acrylate and 25 parts of N-methylpyrrolidone to obtain a mixed monomer, add 0.8 parts of initiator and 0.3 parts of chain transfer agent into 25 parts of N-methylpyrrolidone to obtain an initiator solution, add 50 parts of N-methylpyrrolidone into a reactor, raise the temperature to 90°C, start to drip the mixed monomer and initiator solution at a uniform speed, the dripping time is 5 hours, keep warm for 1 hour after the dripping is completed, cool and filter the material to prepare a polymer dispersant.
[0082] Effect Example 1
[0083] The polymer dispersant of the present invention is characterized:
[0084] (1) Infrared spectroscopy
[0085] The polymer dispersant prepared in Example 1 was placed in an oven at 150°C for drying, and the emulsion structure was tested using a Fourier transform infrared spectrometer in the ATR test mode with a wavelength range of 400 to 4000 cm -1The instrument model is Nicolet iS5 from Thermo Fisher.
[0086] (2) Molecular weight and molecular weight distribution
[0087] The polymer dispersant prepared in the example was dispersed in NMP and diluted to a suitable solid content. The molecular weight and distribution of the polymer dispersant were tested by gel permeation chromatography (GPC). The mobile phase was N-methylpyrrolidone. The flow rate was 0.8 ml / min. The instrument model was Waters alliance GPC E2695.
[0088] The structure of the polymer dispersant prepared in Example 1 was characterized. Figure 1 This is the infrared spectrum of the polymer dispersant prepared in Example 1. It can be clearly seen from the figure that: 2922cm -1 、2854cm -1 It is the stretching vibration peak of methyl and methylene, 1725cm -1 It is the C=O characteristic absorption peak of acrylate, 1677cm -1 It is the C=O characteristic absorption peak of N-vinylpyrrolidone, 1422cm -1 、1349cm -1 It is the bending vibration peak of methyl and methylene, 1102cm -1 It is the CO-characteristic absorption peak of methoxy polyethylene glycol methyl methacrylate. This infrared spectrum verifies that the prepared polymer dispersant is obtained by polymerization of individual monomers.
[0089] Figure 2 This is the molecular weight distribution diagram of the polymer dispersant prepared in Example 1. It can be clearly seen from the figure that the molecular weight distribution of the polymer dispersant prepared in Example 1 is unimodal and the distribution is relatively narrow. Table 1 is the test data of GPC, and it can be seen that the weight average molecular weight is 33581 and the polydispersity coefficient is 1.97.
[0090] Table 1
[0091]
[0092] Effect Example 2
[0093] Preparation of lithium iron phosphate slurry for lithium battery positive electrode: Add PVDF glue, conductive agent, polymer dispersant prepared in Examples 1-6 and Comparative Examples 1-3 (the amount of polymer dispersant is 0.2% of the mass ratio of the positive electrode material) and N-methylpyrrolidone into a stirring tank, use a homogenizer to stir and homogenize until there are no particles, stirring time 1 to 2 hours, add lithium iron phosphate and the remaining N-methylpyrrolidone into a stirring tank, use a homogenizer to stir and homogenize until there are no particles, stirring time 2 to 3 hours, the slurry solid content is 62%.
[0094] (1) Slurry viscosity
[0095] Take 300 grams of the lithium iron phosphate slurry for the positive electrode of the lithium battery as described above, and use a rotational viscometer to test the slurry viscosity in the initial state and the slurry viscosity after standing for 24 hours at room temperature. The test temperature requires 25°C ± 0.2°C, and the rotor is set to 63# and the speed is 60rpm / min.
[0096] (2) Resistivity
[0097] Preparation of pole pieces: The lithium iron phosphate slurry of the lithium battery positive electrode as described above is coated on one side of an aluminum foil, dried, rolled, and cut into pieces to obtain pole pieces.
[0098] The electrode prepared by the above method is subjected to a double-probe electrode resistivity test; wherein the resistivity characterizes the overall penetration internal resistance of the electrode, including the coating resistance, the interface resistance between the coating and the current collector, and the resistance of the current collector itself.
[0099] (3) Peel strength
[0100] Preparation of pole pieces: The lithium iron phosphate slurry of the lithium battery positive electrode as described above is coated on both sides of the aluminum foil, and the pole pieces are obtained by drying, rolling and cutting.
[0101] The pole piece prepared by the above method is rolled, and the 180° peel strength between the material on the pole piece and the foil is tested by a universal tensile machine.
[0102] (4) Pole flexibility
[0103] The double-sided coated electrode prepared by the preparation method in (3) was used for testing. The electrode was folded in half for a number of times until the electrode coating began to leak light. The average value was taken after 5 tests.
[0104] Table 2
[0105]
[0106]
[0107] Note: No polymer dispersant was added to blank slurry 1 and blank slurry 2. The solid content of blank slurry 1 was 57%, and the solid content of blank slurry 2 was 62%.
[0108] According to the above test data, the results show that under similar slurry viscosity, adding 0.2% of the dispersant prepared in Examples 1 to 6 can increase the solid content of the slurry by about 5%, and the viscosity rebound of the slurry is low after 24 hours, and it still has good processability. Compared with the comparative example, the lithium iron phosphate slurry for the positive electrode of the lithium battery prepared using the dispersant in Examples 1 to 6 has better dispersion and stable viscosity effects. In addition, the pole pieces prepared in Examples 1 to 6 have lower resistivity and higher pole piece peeling strength and flexibility.
[0109] Comparative Example 1 uses a conventional dispersant in the prior art. It can be seen that its dispersibility, viscosity stabilization effect and flexibility of the prepared electrode are very poor.
[0110] The difference between Comparative Example 2 and the embodiment is that the amounts of monomers A, C and D are not within the scope of the present invention. It can be seen that the amount of monomer D is relatively large. Although higher flexibility can be obtained, the viscosity reduction and stabilization effects of the obtained dispersant are very poor.
[0111] The difference between Comparative Example 3 and Example 1 is that the dosage of monomers A, B and C is not within the scope of the present invention. The dosage of monomer B alone can be increased, which can also bring good flexibility, but it will also greatly increase the viscosity of the slurry and reduce the stabilizing effect.
[0112] The above descriptions are only a few embodiments of the present invention and do not limit the present invention in any form. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polymer dispersant, characterized in that: The method comprises the following steps: subjecting a raw material composition to a polymerization reaction to obtain the polymer dispersant; the raw material composition comprises a reaction monomer, an initiator and a solvent; the reaction monomer comprises a monomer A, a monomer B, a monomer C and a monomer D, wherein, based on the total mass of the reaction monomers, the mass percentage of the monomer A is 6-10%; the mass percentage of the monomer B is 34-50%; the mass percentage of the monomer C is 20-30%; and the mass percentage of the monomer D is 20-30%; The monomer A is one or more selected from acrylic acid, methacrylic acid, maleic acid and fumaric acid; The monomer B is one or more selected from polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate, polyethylene glycol polypropylene glycol diacrylate, polyethylene glycol polypropylene glycol dimethacrylate, methoxy polyethylene glycol methyl methacrylate, allyl polyethylene glycol, methallyl polyethylene glycol, isopentenyl polyethylene glycol and 4-hydroxybutyl vinyl polyethylene glycol; The monomer C is one or more selected from N,N-dimethylaminoethyl acrylic acid hydrochloride, N,N-dimethylaminoethyl acrylic acid sulfate, β-aminoethyl methacrylic acid hydrochloride, β-aminoethyl methacrylic acid sulfate, N,N-dimethylaminoethyl methacrylic acid hydrochloride, N-vinyl pyridinium salt, N-vinyl pyrrolidone and N-acryloylmorpholine; The monomer D is one or more selected from isooctyl acrylate, decyl methacrylate, isodecyl methacrylate, dodecyl methacrylate, dodecyl acrylate, heptadecanyl methacrylate, heptadecanyl acrylate, octadecyl methacrylate, octadecyl acrylate, behenyl methacrylate, behenyl acrylate, 2-propylheptyl acrylate, 2-propylheptyl methacrylate and 2-phenoxyethyl methacrylate.
2. The method for preparing a polymer dispersant according to claim 1, characterized in that: The monomer B is one or more selected from polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate, polyethylene glycol polypropylene glycol diacrylate, polyethylene glycol polypropylene glycol dimethacrylate, allyl polyethylene glycol, methallyl polyethylene glycol, isopentenyl polyethylene glycol and 4-hydroxybutyl vinyl polyethylene glycol; And / or, the monomer D is one or more selected from isooctyl acrylate, decyl methacrylate, isodecyl methacrylate, dodecyl methacrylate, dodecyl acrylate, heptadecanyl methacrylate, octadecyl methacrylate, octadecyl acrylate, behenyl methacrylate, behenyl acrylate, 2-propylheptyl acrylate, 2-propylheptyl methacrylate and 2-phenoxyethyl methacrylate.
3. The method for preparing a polymer dispersant according to claim 1, characterized in that: Based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 6%-8%; monomer B: 39%-46%, wherein monomer B is methoxy polyethylene glycol methyl methacrylate; monomer C: 23%-25%; and monomer D: 23%-30%. Alternatively, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 7%-10%; monomer B: 40%-45%, wherein monomer B is isopentenyl polyethylene glycol; monomer C: 22%-24%; monomer D: 25%-30%; Alternatively, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 8%-10%; monomer B: 48%-50%, wherein monomer B is polypropylene glycol diacrylate; monomer C: 20%-24%; monomer D: 20%-24%; Alternatively, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 6%-8%; monomer B: 39%-43%, wherein monomer B is polypropylene glycol dimethacrylate; monomer C: 25%-29%; and monomer D: 23%-30%; Alternatively, based on the total mass of the reactive monomers, the reactive monomers include: monomer A: 6%-8%; monomer B: 40%-45%, wherein monomer B is polyethylene glycol polypropylene glycol diacrylate; monomer C: 20%-25%; and monomer D: 23%-30%.
4. The method for preparing a polymer dispersant according to claim 1, characterized in that: Based on the total mass of the reaction monomers, the mass percentage of the monomer A is 6-10%; the mass percentage of the monomer B is 39-50%; the mass percentage of the monomer C is 20-28%; the mass percentage of the monomer D is 20-30%; The monomer A is one or more selected from acrylic acid, methacrylic acid, fumaric acid and maleic acid; The monomer B is one or more selected from methoxy polyethylene glycol methyl methacrylate, isopentenyl polyethylene glycol, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate and polyethylene glycol polypropylene glycol diacrylate; The monomer C is one or more selected from N-vinyl pyrrolidone, β-aminoethyl methacrylate sulfate, N-vinyl pyridinium salt and N-acryloyl morpholine; The monomer D is one or more selected from octadecyl methacrylate, heptadecanyl acrylate and behenyl acrylate.
5. The method for preparing a polymer dispersant according to claim 1, characterized in that: Based on the total mass of the reactive monomers, the reactive monomers include 6% acrylic acid, 39% methoxy polyethylene glycol methyl methacrylate, 25% N-vinyl pyrrolidone and 30% octadecyl methacrylate; Or, based on the total mass of the reactive monomers, the reactive monomers include 8% acrylic acid, 46% methoxypolyethylene glycol methyl methacrylate, 23% β-aminoethyl methacrylate sulfate and 23% octadecyl methacrylate; Or, based on the total mass of the reactive monomers, the reactive monomers include 9% methacrylic acid, 42% isopentenyl polyethylene glycol, 23% N-vinyl pyridinium salt and 26% octadecyl methacrylate; Or, based on the total mass of the reactive monomers, the reactive monomers include 10% fumaric acid, 50% polypropylene glycol diacrylate, 20% N-vinyl pyrrolidone and 20% heptadecanyl acrylate; Or, based on the total mass of the reactive monomers, the reactive monomers include 6% methacrylic acid, 41% polypropylene glycol dimethacrylate, 28% N-vinyl pyrrolidone and 25% behenyl acrylate; Or, based on the total mass of the reactive monomers, the reactive monomers include 7% of maleic acid, 43% of polyethylene glycol polypropylene glycol diacrylate, 22% of N-acryloylmorpholine and 28% of octadecyl acrylate.
6. The method for preparing a polymer dispersant according to claim 1, characterized in that: The polymerization temperature is 85-95°C; And / or, the solvent is N-methylpyrrolidone; And / or, the initiator is one or more of cumene hydroperoxide, tert-butyl hydroperoxide, azobisisobutyronitrile, and azobisisoheptanenitrile; And / or, the raw material composition comprises a chain transfer agent, and the chain transfer agent can be one or more of 2-mercaptoethanol, n-butyl mercaptan, tert-butyl mercaptan, and dodecyl mercaptan.
7. A polymer dispersant, characterized in that It is prepared by the preparation method described in any one of claims 1 to 6; the weight average molecular weight of the polymer dispersant is preferably 5000-50000, such as 33581, 28450, 42420, 18340, 35530 or 10240; the molecular weight distribution index of the polymer dispersant is preferably 1.2-2, such as 1.97, 1.65, 1.86, 1.75, 1.99 or 1.
35.
8. An electrode slurry, characterized in that: It comprises an electrode active material, a polymer dispersant as claimed in claim 7 and a solvent; Wherein, the electrode active material is preferably a positive electrode active material, and the positive electrode active material is preferably one or more of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, nickel cobalt manganese ternary material, and nickel cobalt aluminum oxide lithium ternary material; Wherein, the electrode slurry preferably further includes a conductive agent; the conductive agent is preferably one or more of carbon black or carbon nanotubes.
9. An electrode plate, characterized in that: It is prepared using the electrode slurry as claimed in claim 8.
10. A battery, characterized in that: It comprises the electrode plate as claimed in claim 9, and the battery is preferably a lithium-ion battery.